Contemporary Use of ctDNA for the Colorectal Surgeon - Heit, Madilyn; Cohen, Stacey A. (Clinics in Colon and Rectal Surgery, 2024)
While advances in treatment and diagnostics have improved prognosis in colorectal cancer (CRC), room for advancement remains, highlighting the importance of improving tools for early detection and treatment guidance. Current national guidelines rely on stage-based treatment recommendations but fail to identify patients with lower stage disease who have a higher likelihood of recurrence or those for whom additional therapy may not be beneficial. Circulating tumor DNA (ctDNA) is an emerging noninvasive blood-based assay, which can inform cancer status as a single time point and/or longitudinal biomarker. ctDNA can be used for the diagnosis of cancer, detection of minimal/molecular residual disease, molecular profiling, and assessing treatment response. In patients for whom operative management is indicated, detectable ctDNA is associated with worse survival outcomes. This review highlights the expanding field of ctDNA in CRC, underlining pivotal data and areas with the need for more research that are key for colorectal surgeons to understand.
Keywords: circulating tumor DNA; adjuvant chemotherapy; biomarker; colon cancer; liquid biopsy